Determinants of the corporate image of Islamic banks in Kota Kinabalu, Sabah - Dk Intan Saidatul Farahin Pg Morshide (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2016)
The Islamic banking system is growing and gaining customers' acceptance from all over the world. Many international conventional banks have started to open branches which operate in accordance with the Islamic Shari'ah principles mostly in Islamic countries. The Islamic banking system is expected to face strong competition not only among the Islamic banks but also from well-established conventional banks offering Islamic products and services. This research aims to determine customers' perception towards the corporate image of Islamic banks in a dual banking environment like Malaysia. Focus in this research was to identify the determinants that influence the corporate image of Islamic banks in Kota Kinabalu, Sabah. In this study, seven determinants were hypothesized to influence the corporate image of Islamic banks which are corporate identity, reputation, services offered, physical environment, contact personal and Shari'ah compliance. Self-administrated questionnaires were distributed to 300 customers of Islamic banks around Kota Kinabalu, Sabah by way of judgmental sampling. Data was then analysed using Statistical Package for Social Sciences (SPSS) software version 19.0. The finding indicated that there is a positive overall perception towards corporate image of the Islamic banks. However, the study found that only three determinants have significant and positive relationship with corporate image which are corporate identity, reputation and contact personal. Reputation was found to be the most influential determinant that can affect the corporate image of Islamic banks. Therefore, it is suggested that the Islamic banks in Malaysia has to improve their corporate identity by portraying a good image to the public. Other than that, to enhance Islamic bank's corporate image, Islamic banks also need to build and maintain their reputation by keeping their promises to their customers. Lastly, Islamic bank should train and build positive behavior, competencies and appearance of its employees as they are the front line people that deal with customers and represent the Islamic banks.